First day in clinical practice: evaluating stress of nursing students and their ways to cope with it - (:unkn) unknown (DRUNPP-SARAJEVO, 2012)
Background: Initial clinical experience mostly is highly stressful for nursing student. Objectives: The study was conducted to evaluate the stress experienced by nursing students, who are about to carry out their first clinical practices, and also, their ways to cope with it. Methods: The study was experimentally conducted with students studying at 1st grade of nursing department of a university in Turkey in the order including final test control group. Sampling of the study consisted of a test group and a control group (n=26) accounting for 52 students in total. Data were obtained by the clinical stress questionnaire, the inventory of the styles for coping with stress and Student Questionnaire Form. Frequency, arithmetical mean, Mann-Whitney U, Kruskal Wallis, Spearman's Correlation Analysis and Cronbach alpha test were used in analyzing the data. Results: It was found that mean score of the test group relating to stress level (31.88 +/- 8.60) is lower than that of the control group (32.30 +/- 11.57); however, the difference between them is not statistically significant (p>0.05). When it was assessed from the point of view of coping with stress, it was seen that mean score of sub-dimension of optimistic approach of the students in the control group (8,26 +/- 2,34) is higher than that of the students in the test group (6,34 +/- 1,89) in a statistically significant way (U= -2.80; p=0,005). Conclusions: It was concluded that students experience stress on their very first day that they will begin clinical experience with no respect to circumstances despite training and orientation works to be conducted, more concentration should be paid to laboratorial education in the first grade, simulation practices should be developed, clinical environment should be made suitable for the student and moreover, effective methods in coping with stress should be taught and practiced.
Keywords: clinical practice; coping style; nursing students; stress